THE VICTORY OF SOLIDARISM IN GLOBAL GOVERNANCE CASE STUDY OF FOREST FIRES AND TRANSBOUNDARY HAZE IN INDONESIA - Yanyan Mochammad Yani (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2017)
Solidarism and pluralism are key concepts of English School theory. Solidarism have many differences with pluralism which sometimes contradicting each other. Solidarism has inspired many international projects in dealing with many international problems including Roundtable Sustainable Palm Oil (RSPO) in the context of forest fires and transboundary haze in Indonesia. Solidarists perceived that RSPO is an effective solution in combatting forest fires and transboundary haze in Indonesia. This article would like to question the hegemony of solidarism in global governance with the case study of RSPO in mitigating forest fires and transboundary haze in Indonesia. This articles has three findings. Firstly, RSPO as solidarism projects has its advantages and weaknesses that need for constant reform and revision. Secondly, pluralism is not neglecting the global governance as there is ASEAN Agreement on Transboundary Haze Pollution that combined global governance with sustainable development and legitimacy. Thirdly, the rivalry of solidarism and pluralism can be neatly put under the heading of global governance. Keywords: pluralism, solidarism, English School, forest fires, transboundary haze Abstrak Solidarisme dan pluralisme adalah konsep penting dalam teori English School. Solidarisme memiliki banyak perbedaan yang bertolak belakang dengan pluralisme. Solidarisme telah mendorong pelaksanaan berbagai inisiatif sebagai solusi dari berbagai masalah internasional termasuk Roundtable Sustainable Palm Oil (RSPO) dalam konteks mitigasi kebakaran hutan dan pencemaran udara di Indonesia. Solidarisme mengajukan hegemoni global governance yang ditunjukkan dalam dukungan penuh terhadap RSPO di dalam mencegah terjadinya kebakaran hutan dan pencemaran udara di Indonesia. Artikel ini hendak mengkritisi hegemoni solidarisme dalam global governance melalui studi kasus RSPO dalam mitigasi kebakaran hutan dan pencemaran udara di Indonesia. Penelitian ini memiliki tiga kesimpulan. Pertama, RSPO sebagai salah satu inisiatif solidarisme memiliki kelebihan dan kelemahan yang memerlukan reformasi dan revisi konstan. Kedua, pluralisme memiliki analisis yang mendalam terkait global governance dengan studi ratifikasi ASEAN Agreement on Transboundary Haze Pollution oleh Indonesia pada tahun 2014. Ketiga, rivalitas antara pluralisme dan solidarisme dapat dipersatukan dalam sebuah konsep global governance. Kata kunci: pluralisme, solidarisme, English School, kebakaran hutan, pencemaran udara.